Investigation of viscosity and temperature characteristics of fuel with increased crystallization temperature point and serviceability of the fuel system elements of aeroplanes using such fuel, with simulation low temperature and hard hydrodynamic operati - Козаченко, А. И.; Максютинский, П. Ф. (Proceedings of National Aviation University (archive), 1998)
The aim of research is to determine fuel viscosity and temperature characteristics with increased CTP and serviceability of pump units and fuel filters, simulated on real temperature and hydrodynamic conditions at expected operating conditions of airplane fuel system. It was established by experiments the effect of hydromechanical action on hydrogen fuel in the process of cooling: in mixing fuel with pump units the viscosity sharp increase takes place at the temperature 6-8°C lower than it’s cooled in static conditions